Pemanfaatan Media Pembelajaran Audio Visual Berbasis Aplikasi Canva - Alfian, Ari Nurul; Putra, Mardi Yudhi; Arifin, Rita Wahyuni; Barokah, Agung; Safei, Ahmad; Julian, Novan (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2022)
The ability to master technology and information, especially learning media for educators in mastering the concept of learning media is very necessary. The problems faced by educators from HIMPAUDI are still not utilizing learning media in the learning process. In addition, they still don't understand how to make learning media using the Canva application. The solution to the problems above is to create learning media and learning videos using Canva. The method in implementing this Community Service activity with the main target being educators at HIMPAUDI, West Bekasi District where there are 2 resource persons, 2 moderators and 2 technical support people. PkM was held on Saturday, December 22, 2021. PkM was conducted by providing training and demonstrations to participants in using Canva applications with the support of online media in the form of zoom, YouTube and Google Drive links. The outputs of this PkM are YouTube Streaming and a draft of the BRIN Sinta Ristek Indexed PkM Journal.